1986
DOI: 10.1038/323816a0
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral effects of recombinant tumour necrosis factor in vitro

Abstract: Tumour necrosis factor (TNF) was first described as a factor in the serum of mice injected with tubercle bacilli (BCG) and several days later with lipopolysaccharide (LPS). The gene encoding TNF has recently been cloned and pure recombinant human TNF is now available. TNF is known for its in vivo antitumour effect and in vitro cytotoxicity on certain transformed cell lines. Similarities in amino acid sequence and biological activity to lymphotoxin and cachectin have been reported, and very recently a growth-fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
168
2
1

Year Published

1987
1987
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 372 publications
(174 citation statements)
references
References 14 publications
3
168
2
1
Order By: Relevance
“…In fact, Kohase et al (1986) and Mestan et al (1986) showed that recombinant human TNF can produce an anti-viral effect in human diploid fibroblasts. This action of TNF could be abolished in the presence of antiserum specific for IFNbeta.…”
Section: General Properties Of Tnfmentioning
confidence: 99%
“…In fact, Kohase et al (1986) and Mestan et al (1986) showed that recombinant human TNF can produce an anti-viral effect in human diploid fibroblasts. This action of TNF could be abolished in the presence of antiserum specific for IFNbeta.…”
Section: General Properties Of Tnfmentioning
confidence: 99%
“…3 Targeting IFN-signaling actually provides a general selective advantage for tumor formation, because it favors the disruption of the intercellular cross-talk between HPV positive and immunological effector cells. 4 In a previous investigation, we demonstrated that the antiviral effect of TNF-a, which is mediated by IFN-b gene activation, 5 is disturbed in HPV positive cervical carcinoma cells. 6 The reason for this failure is the lack of interferon-regulatory factor (IRF)-1 and p48 (IRF-9) expression, two key regulators, tightly involved in the transcriptional control of the intermediate and the delayed interferon response.…”
mentioning
confidence: 94%
“…IFN-a and IFN-g prevent EBV-induced activation of B cells in a direct, cell-independent manner; however, IFN-g appeared much more potent [3,4]. Furthermore, tumour necrosis factor (TNF) which also exerts antiviral effects on RNA-and DNA-viruses [5] selectively inhibits EBV activation of B cells [6]. On the other hand, EBV evolved particular strategies escaping the immunosurveillance of the host [1].…”
Section: Introductionmentioning
confidence: 99%